Response of wheat aphid to insecticides is influenced by the interaction between temperature amplitudes and insecticide characteristics - Xing, Kun; Zhang, Shu-Ming; Jia, Mei-Qi; Zhao, Fei (Frontiers in Physiology, 2023)
Introduction: Climate change not only directly affects the phenotype of organisms but also indirectly impacts their physiology, for example, by altering their susceptibility to insecticides. Changed diurnal temperature fluctuations are an important aspect of climate change; ignoring the impact of these fluctuations on the biological effects of various chemical insecticides can lead to inaccurate assessments of insecticide risk under the current and future climate change scenarios. Methods: In this study, we studied effects of different temperature amplitudes (± 0, ± 6, ± 12°C) at the same mean temperature (22°C) on the life-history characteristics of a globally distributed pest (Sitobion avenae, wheat aphid), in response to low doses of two insecticides. The first, imidacloprid shows a positive temperature coefficient; the second, beta-cypermethrin has a negative temperature coefficient. Results: Compared with the results seen with the constant temperature (22°C), a wide temperature amplitude (± 12°C) amplified the negative effects of imidacloprid on the survival, longevity, and fecundity of wheat aphid, but significantly increased the early fecundity of the wheat aphid. Beta-cypermethrin positively impacted the wheat aphid at all temperature amplitudes studied. Specifically, beta-cypermethrin significantly increased the survival, longevity, and fecundity of the wheat aphid under medium temperature amplitude (± 6°C). There were no significant differences in the survival, longevity, and early fecundity of the wheat aphid when it was treated with beta-cypermethrin at the large temperature amplitude (± 12°C). However, the negative effect of beta-cypermethrin on the intrinsic rate of increase of wheat aphid decreased gradually with the increase in temperature amplitude. Discussion: In conclusion, the response of the wheat aphid to positive temperature coefficient insecticides was markedly affected by temperature amplitude, while negative temperature coefficient insecticides increased the environmental adaptability of wheat aphid to various temperature amplitudes. Our results highlight the importance of the integrated consideration of diurnal temperature fluctuations and different temperature coefficient insecticide interactions in climate-change-linked pesticide risk assessment; these results emphasize the need for a more fine-scale approach within the context of climate change and poison sensitivity.